German scholars and ethnic cleansing 1919-1945 - Haar, Ingo; Fahlbusch, Michael (Berghahn Books, 2007)
Recently, there has been a major shift in the focus of historical research on World War II towards the study of the involvements of scholars and academic institutions in the crimes of the Third Reich. The roots of this involvement go back to the 1920s. At that time right-wing scholars participated in the movement to revise the Versailles Treaty and to create a new German national identity. The contribution of geopolitics to this development is notorious. But there were also the disciplines of history, geography, ethnography, art history, archeology, sociology, and demography that devised a
Keywords: Political culture : Germany : History : 20th century; Racism : Germany : History : 20th century; Genocide : Germany : History : 20th century; Germany : Ethnic relations; Germany : Race relations